Mycosynthesis of zinc sulfide/zinc oxide nanocomposite using Fusarium oxysporum for catalytic degradation of methylene blue dye, antimicrobial, and anticancer activities - Hosam Salaheldin; Aya Aboelnga; Ashraf Elsayed (Scientific Reports)
Abstract In the present study, extracellular cell-free filtrate (CFF) of fungal Fusarium oxysporum f. sp. cucumerinum (FOC) species, was utilized to biosynthesize zinc oxide /zinc sulfide (ZnO/ZnS) nanocomposite. This was achieved by mixing the metal salt with the fungal CFF for 96 h at a temperature of 27 ± 1.0 °C and a pH of 6.5. Several analytical techniques, such as XRD, TEM, UV-Vis, FTIR, DLS, and zeta potential studies, have confirmed the synthesis of NPs. Fungal CFF enzymes and metabolites stabilized produced NPs, according to FTIR. The nanocomposite particle diameter (15–80 nm) was estimated using HR-TEM imaging. The DLS and XRD measurements verified those findings. The zone of inhibition diameter for MRSA was 35 ± 0.21 mm, while B. subtilis measured 33 ± 0.32 mm against the nanocomposite. For E. coli and S. typhi bacterial isolates, it was 25 ± 0.19 and 32 ± 0.36 mm, respectively. The determined MIC value for E. coli was 5,000 µg/mL and MRSA was 500 µg/mL. The ZnO/ZnS nanocomposite has a dose-dependent cytotoxic effect on breast cancer cells, with an IC50 of 197 ± 0.895 µg/mL. The Methylene blue dye was removed by 87.51% using the nanocomposite. Thus, green biosynthesized ZnO/ZnS nanocomposites are recommended for pharmaceutical, industrial, and biological applications.